2016
DOI: 10.1016/j.scienta.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-induced decrease in CO2 assimilation in ‘Rangpur’ lime is associated with low stomatal conductance rather than low photochemical performances

Abstract: Aluminum (Al) is toxic to most plants. Although inhibition of root elongation can occur even under 10 M Al, above 1000 M damage to photochemical performances has been reported, reducing the CO 2 assimilation rate (A). However, Al is retained in the roots of most plants, including Citrus limonia ('Rangpur' lime) with no direct explanation for the low A. In this study, 'Rangpur' lime plants were cultivated hydroponically in a nutrient solution with 1480 M Al, and we expected to determine the time range within wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
7
28
0
Order By: Relevance
“…The nutrient solution showed a chemical composition based on the solution proposed by Clark (1975), and it has been already used to test Al resistance in 'Rangpur' lime plants (Banhos et al, 2016 (Banhos et al, 2016), we observed that 1480 μM Al causes Al-induced decrease in gas exchange rates in 'Rangpur' lime plants after 45 days. Then, the solution contained 0 and 1480 μM Al provided through 1479.5 μM AlCl 3 6 H 2 O.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 88%
See 2 more Smart Citations
“…The nutrient solution showed a chemical composition based on the solution proposed by Clark (1975), and it has been already used to test Al resistance in 'Rangpur' lime plants (Banhos et al, 2016 (Banhos et al, 2016), we observed that 1480 μM Al causes Al-induced decrease in gas exchange rates in 'Rangpur' lime plants after 45 days. Then, the solution contained 0 and 1480 μM Al provided through 1479.5 μM AlCl 3 6 H 2 O.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 88%
“…Then, the solution contained 0 and 1480 μM Al provided through 1479.5 μM AlCl 3 6 H 2 O. The pH of the solution was monitored daily and maintained at 4.0 ± 0.1 to keep Al as soluble as possible, and the solution was totally replaced every 15 days (Banhos et al, 2016). The nominal chemical composition of this solution was also tested on Geochem-EZ software (Shaff et al, 2010), resulting in more than 85% free Al 3+ available.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'Rangpur Lime' (Citrus limonia Osbeck) is the most used rootstock in the Brazilian citrus orchards due to its compatibility to most scion cultivars, satisfactory yield, induction of early-bearing and adequate performance under water deficit condition, presenting substantial importance for the rain-fed Citrus growing area (Mourão Filho et al, 2007;Oliveira et al, 2015;Banhos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Through the data obtained by pH-measuring devices or acid-base indicator solutions, it is possible to evaluate the physiological condition of each seed and, consequently, the physiological potential of lots (Araldi and Coelho, 2015;Alves et al, 2016).…”
Section: Introductionmentioning
confidence: 99%